Advances and setbacks in the recognition of the territory of the Bolivian Ayoreos - Apaza Huanca, Yaneth Katia (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
The Bolivian Ayoreos face a struggle for the recognition of their territory, their legal demand began at the end of the eighties; in 1999 through Law No. 1715 they achieved the recognition of four of their communities as Community Lands of Origin (TCO). In 2009, the new Constitution would change the name of the TCO to the Indigenous Territory of Origin Peasant (TIOC). It has been approximately 20 years since they achieved any kind of territorial recognition, although the Constitution recognizes them as a "nation" and the ancestral domain over their territories.